FAKTOR-FAKTOR YANG MEMPENGARUHI PREDIKSI KEBANGKRUTAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR - Hon, Elvin; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research aims to examine the effect of cash flow, profitability, and leverage on the predicition of corporate bankruptcy in manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. This study used a purposive samnpling method and obtained 19 companies and total of samples in this study were 57 samples. The method in this study used logistic regression analytics with Eviews12 and Microsoft Excel. The results of this study shows that cash flow, profitability, and leverage has an insignificant effect on prediction of corporate bankruptcy. Then, the cash flow variables. profitability, and leverage simultaneously has an effect on prediction of corporate bankruptcy.